Exploring Hotel Guest Satisfaction through Thematic Analysis - Prasadja, Heru; Aldiani, Desyana Pratiwi Azzahra; Laturiuw, Astuti Kusumawicitra (Journal of Business and Economics Research (JBE), 2025)
This study investigated guest satisfaction drivers at Hotel Santika Premiere ICE BSD through a thematic analysis of 1,008 guest reviews. The research addressed the growing need for data-driven insights in the hospitality industry to better understand guests' diverse needs and expectations. Through qualitative analysis, five key themes emerged as pivotal satisfaction drivers: service quality and staff responsiveness (each with 250 mentions, 24.8%), cleanliness (200 mentions, 19.8%), amenities (150 mentions, 14.9%), and value for money (150 mentions, 14.9%). Service quality and staff responsiveness demonstrated the most substantial influence on guest satisfaction, shaping the emotional and relational dimensions of the experience, while cleanliness and amenities established fundamental expectations. Demographic analysis revealed significant variations, with older adults and international travelers reporting higher satisfaction levels (92% and 93% respectively) than younger guests and domestic travelers (85% and 87% respectively). These differences highlighted the importance of demographically tailored services, such as enhanced technology integration for younger guests and culturally adapted offerings for international travelers. Based on the findings, strategic recommendations include improving soundproofing, diversifying breakfast options, and implementing comprehensive staff training programs to address concerns identified in 27% of guest feedback. This research contributes to hospitality management theory and practice by demonstrating the effectiveness of data-driven decision-making in optimizing service delivery while balancing standardized excellence with personalized guest experiences. The study provides a framework for sustainable competitive advantage in the evolving hospitality landscape through strategic alignment of service delivery with diverse guest expectations.